2018
DOI: 10.1021/acs.nanolett.8b02902
|View full text |Cite|
|
Sign up to set email alerts
|

Unveiling the Intrinsic Cycle Reversibility of a LiCoO2 Electrode at 4.8-V Cutoff Voltage through Subtractive Surface Modification for Lithium-Ion Batteries

Abstract: The thermodynamic instability of the LiCoO2 layered structure at >0.5Li extraction has been considered an obstacle for the reversible utilization of its near theoretical capacity at high cutoff voltage (>4.6 V vs Li/Li+) in lithium-ion batteries. Many previous studies have focused on resolving this issue by surface modification of LiCoO2, which has proven to be effective in suppressing phase transformation. To determine the extent to which surface protection of LiCoO2 is effective despite its thermodynamic ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 58 publications
2
61
0
Order By: Relevance
“…In contrast, the suppressed lattice contraction and expansion in the electrode cycled at 4.9 V hints at the possible positive high‐voltage effects, as demonstrated in earlier studies on the LCO system. [ 33 ] The structural disorder in the electrode attributed to the atomic disorder or lattice strain is further confirmed by the Williamson–Hall plot in Figure S8, Supporting Information. An increase of the slope, indicating an increase in the amount of microstrain, was observed from the electrode after electrochemical cycling at a cut‐off voltage of 4.25 V (Figure S8a, Supporting Information), and the slope was maintained up to 50 cycles.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…In contrast, the suppressed lattice contraction and expansion in the electrode cycled at 4.9 V hints at the possible positive high‐voltage effects, as demonstrated in earlier studies on the LCO system. [ 33 ] The structural disorder in the electrode attributed to the atomic disorder or lattice strain is further confirmed by the Williamson–Hall plot in Figure S8, Supporting Information. An increase of the slope, indicating an increase in the amount of microstrain, was observed from the electrode after electrochemical cycling at a cut‐off voltage of 4.25 V (Figure S8a, Supporting Information), and the slope was maintained up to 50 cycles.…”
Section: Resultsmentioning
confidence: 72%
“…Note that the surface structure of the electrode cycled at 4.9 V remained much more stable despite the voltage being above 4.6 V. We speculate that this stability mainly originates from the dissolution of Ni at a specific high voltage over 4.6 V reported in previous studies. [ 23,33 ] Charging up to 4.6 V induces the transition metal migration, resulting in resistive spinel and rock‐salt formation on the particle surface; however, at certain voltages above 4.6 V, the resistive layer is observed to dissolve, leaving only the original layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In addition, it was reported that resistive Co 3 O 4 is electrochemically leached out from the surface of LiCoO 2 during cycling. 36 The generation and dissolution of NiO during cycling between 2.5-4.5 V in the uncoated sample may cause surface damage of the cathode particles due to the structural changes. As a result, it was considered that the surface resistance of the uncoated sample greatly increased and led to the observed capacity decrease.…”
Section: Hard X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…Unfortunately, excess delithiation usually leads to the release of undercoordinated oxygen, causing structural instability . Furthermore, the continuous growth of the resistive layer at high voltage is considered the root cause of capacity decay in the range of 4.3–4.9 V, whereas over the range of 3–4.5 V, the root cause of capacity decay is attributed to LCO structural changes . Both X‐ray powder diffraction (XRD) and neutron powder diffraction (NPD), alongside transmission electron microscopy (TEM), have been used to study the LCO structure as a function of lithiation, showing that Li ion ordering in Li x CoO 2 at x = 0.5 induces an irreversible hexagonal to monoclinic symmetry phase transformation, reducing the specific capacity of the entire battery .…”
Section: Introductionmentioning
confidence: 99%